Repeat Migration in the United States: Who Moves Back and Who Moves On? - DaVanzo, Julie (The Review of Economics and Statistics, 1983)
Migration often occurs more than once in an individual's lifetime. Many people may move back to the location where they were born after a stay in another area, or they may move on to yet another new location. In this paper the migrant's location-specific capital and information costs are examined, and empirical findings for the United States are presented and discussed.